The Impact of Characteristics, Independence, Diversity, and Activities of the Board of Director on the Sustainable Development Goals Disclosure - Kenny Ardillah (Dinasti Publisher, 2022)
The role of the board of director is very important in disclosing the Sustainable Development Goals because most of the company's leadership with a higher number of directors, the existence of independent directors, directors with diversity, and an adequate number of board of director meetings can determine the company's sustainability strategy. This study aims to analyze the commitment of the board of director to Sustainable Development Goals disclosure in public companies by proving the influence of characteristics (size of the board of director), independence (proportion of independent directors), diversity (presence of female directors), and activity of the board of director (number of board of director meetings) on Sustainable Development Goals disclosure. This research is a quantitative research with documentation as data collection method. The sample of this research is a financial sector public company listed on the Indonesia Stock Exchange from 2019-2021. The data analysis method used in this study is multiple linear regression with the panel data approach. The results of this study are that there is a positive effect of the presence of directors at board of director meetings on the disclosure of Sustainable Development Goals which has been controlled by profitability and firm size. The results of other studies are that there is no effect of the size of the board of director, the proportion of independent directors, the presence of female directors, and the number of board of director meetings on the Sustainable Development Goals disclosure which have been controlled by profitability and firm size.